Answer:
The correct option is C) ![f(x)=4x \ \text{and} \ g(x)=\frac{x}{4}](https://tex.z-dn.net/?f=f%28x%29%3D4x%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D%5Cfrac%7Bx%7D%7B4%7D)
Step-by-step explanation:
We need to find out the pair of functions which are inverse of each other
A) ![f(x)=x \ \text{and} \ g(x)=-x](https://tex.z-dn.net/?f=f%28x%29%3Dx%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D-x)
Since, ![(fog)(x)=f(g(x))=-x](https://tex.z-dn.net/?f=%28fog%29%28x%29%3Df%28g%28x%29%29%3D-x)
and
So, these are not inverse of each others
B) ![f(x)=2x \ \text{and} \ g(x)=\frac{-x}{2}](https://tex.z-dn.net/?f=f%28x%29%3D2x%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D%5Cfrac%7B-x%7D%7B2%7D)
Since, ![(fog)(x)=f(g(x))=2(\frac{-x}{2})=-x](https://tex.z-dn.net/?f=%28fog%29%28x%29%3Df%28g%28x%29%29%3D2%28%5Cfrac%7B-x%7D%7B2%7D%29%3D-x)
and
So, these are not inverse of each others
C) ![f(x)=4x \ \text{and} \ g(x)=\frac{x}{4}](https://tex.z-dn.net/?f=f%28x%29%3D4x%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D%5Cfrac%7Bx%7D%7B4%7D)
Since, ![(fog)(x)=f(g(x))=4(\frac{x}{4})=x](https://tex.z-dn.net/?f=%28fog%29%28x%29%3Df%28g%28x%29%29%3D4%28%5Cfrac%7Bx%7D%7B4%7D%29%3Dx)
and
So, these are inverse of each others
D) ![f(x)=-8x \ \text{and} \ g(x)=8x](https://tex.z-dn.net/?f=f%28x%29%3D-8x%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D8x)
Since, ![(fog)(x)=f(g(x))=-8(8x)=-64x](https://tex.z-dn.net/?f=%28fog%29%28x%29%3Df%28g%28x%29%29%3D-8%288x%29%3D-64x)
and
So, these are not inverse of each others
Therefore the correct option is C) ![f(x)=4x \ \text{and} \ g(x)=\frac{x}{4}](https://tex.z-dn.net/?f=f%28x%29%3D4x%20%5C%20%5Ctext%7Band%7D%20%5C%20g%28x%29%3D%5Cfrac%7Bx%7D%7B4%7D)